Microwave thermotherapy and its clinical applications - Singh S.P. (My University, 2025)
In this paper, a review of the use of microwave energy for thermotherapy (hyperthermia/ablation therapy is reported. The advantages of hyperthermia/ablation therapy over radio- and chemo-therapies, and the techniques for estimation of specific absorption rate (SAR) are discussed. The review includes its history, description of various types of applicators and temperature sensors developed for hyperthermia/ablation therapy, and clinical applications of hyperthermia/ablation therapy. In addition, Oncothermia, which is a method of hyperthermia for oncological use is also introduced. © 2019 URSI. All rights reserved.